Effectiveness of Scaffolding Worksheet on Students’ Scientific Explanation Skills in Static Electricity and Application to Living Things - Wahyuni Handayani; Tri Wahyu Agustina (Postgraduate, University of Mataram, 2023)
This study conducted a quasi experiment to investigate the effectiveness of scaffolding worksheet on students’ scientific explanation. A total of 30 participants were randomly assigned into two groups. One class is the experimental class that received of scaffolding worksheet and one other class as the control class. The comparative analysis results revealed that scaffolding explanation worksheets are effective in improving students’ science explanation skills. The average score of scientific explanation of students in experimental class and control class is 69.10 and 53.00. Regarding the SOLO taxonomic classification, in spite of the fact that the experimental class students on average exceeded the control class students, it can be seen that some students in the experimental class were still at the prestructural and unistructural levels. The incorrect timing to remove scaffolds and misusage of scaffolding worksheet were two possible reasons behind the failure of fading scaffolding practice